Securing civilization? the EU, NATO, and the OSCE in the post-9/11 world - Gheciu, Alexandra; Oxford eBooks (Oxford : Oxford University Press, 2008)
This text examines the evolution of security practices carried out in the Euro-Atlantic area in the name of fighting international terrorism. With particular emphasis on three key institutions of the transatlantic security community: the EU NATO and the OSCE.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; North Atlantic Treaty Organization; Organization for Security and Co-operation in Europe; Security, International; War on Terrorism, 2001-; International relations -- Risk assessment; Electronic books